Coarsening- and creep resistance of precipitation-strengthened Al–Mg–Zr alloys processed by selective laser melting. (15th April 2020) - Griffiths, S.; Croteau, J.R.; Rossell, M.D.; Erni, R.; De Luca, A.; Vo, N.Q.; Dunand, D.C.; Leinenbach, C.
Abstract: The coarsening behavior of Al3 Zr precipitates during aging was investigated for two Al–Mg–Zr alloys (Al–3.6Mg–1.2Zr and Al–2.9Mg–2.1Zr, wt%) processed by selective laser melting (SLM). Scanning transmission electron microscopy (STEM) investigations of peak-aged (400 °C, 8 h) samples reveal both continuous ( 2 nm in diameter) and discontinuous ( 5 nm wide and hundreds of nanometers in length) coherent, secondary L12 -Al3 Zr precipitates. In-situ STEM experiments showed that aging at 400 °C results in the appearance and growth of both grain-boundary Al3 Zr precipitates, and intragranular nanometer-sized spherical Al3 Zr precipitates in Zr-rich dendritic arms. Heating to 500 °C resulted in the disappearance of most Al3 Zr precipitates and oxide particles. This microstructural evolution sheds light on the evolution of the alloy strength at elevated temperature. For short-term yield tests, as-fabricated samples displayed higher yield strengths than peak-aged samples at temperatures above 150 °C (e.g., 87 vs 24 MPa at 260 °C). This is attributed to coarsening of grain-boundary precipitates during aging, decreasing their ability to inhibit grain-boundary sliding (GBS) of the fine equiaxed grains ( 1 µm). For longer term creep tests at 260 °C, both as-fabricated and peak-aged samples displayed near-identical creep behavior during a long-duration (168 h) creep test; by contrast, during a shorter duration creep test (8 h), as-fabricated samples are more creep-resistant than samples previously aged at 260 °C (threshold stresses of 40 vs. 14 MPa, respectively). Again, the creep behavior is consistent with coarsening of grain-boundary precipitates, occurring now during long-duration creep tests at 260 °C. An exact creep mechanism could not be isolated due to microstructural changes during testing but is believed to be a combination of GBS and dislocation motion. Graphical abstract: Image, graphical abstract